(untitled) (Journal of Computational Mathematics, 1994)
In this work, a Signorini problem with Coulomb friction in two dimensional elasticity is considered. Based on a new representation of the derivative of the double-layer potential, the original problem is reduced to a system of variational inequalities on the boundary of the given domain. The existence and uniqueness of this system are established for a small frictional coefficient. The boundary element approximation of this system is presented and an error estimate is given.